2017
DOI: 10.46989/001c.20868
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Distiller’s Dried Grains with Solubles on Carcass Composition, Fatty Acid Composition, Skin and Fillet Coloration of Rainbow Trout (Oncorhynchus mykiss)

Abstract: The aim of the study was to evaluate the effects of distiller’s dried grains with solubles (DDGS) as an alternative protein source on carcass composition, fatty acid composition, skin, and fillet coloration of rainbow trout (Oncorhynchus mykiss). Four isoproteic (45.5% crude protein) and isocaloric (17.42 MJ/kg) diets were formulated using DDGS (0, 10, 20 and 30%) for a feeding trial of 84 days. Fish (mean initial weight of 19.88 g) were distributed into triplicate treatments at a rate of 25 fish per 200 L tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…idella , and Murray et al (2014) in Salvelinus alpinus . As in the current study, several authors have noted that fillet FA profiles reflect dietary FA profiles in a wide range of fish species (Aydın et al, 2017; Guerreiro et al, 2020; Özogul et al, 2007; Yıldız et al, 2018), with n‐6 FAs having higher levels than n‐3 FAs. Omega‐3 PUFAs are critical in human nutrition, and there were no significant differences in n‐3 PUFA among the treatments.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…idella , and Murray et al (2014) in Salvelinus alpinus . As in the current study, several authors have noted that fillet FA profiles reflect dietary FA profiles in a wide range of fish species (Aydın et al, 2017; Guerreiro et al, 2020; Özogul et al, 2007; Yıldız et al, 2018), with n‐6 FAs having higher levels than n‐3 FAs. Omega‐3 PUFAs are critical in human nutrition, and there were no significant differences in n‐3 PUFA among the treatments.…”
Section: Discussionsupporting
confidence: 71%
“…Fish carcasses are influenced by dietary composition and feed intake (Aydın et al, 2017). In this study, the proximate composition of C .…”
Section: Discussionmentioning
confidence: 99%
“…According to Oliveira et al (2020), Sándor et al (2021 a, b), Gyalog et al (2023), replacing high levels of DDGS with plant ingredients leads to improved growth performance and lower feed costs in carp and European catfish diets. Similarly, Aydın and Gümüş (2020) found that the feed cost decreased with increased levels of DDGS in feed compared to the control diet of rainbow trout. Total replacement of SBM with DDGS in feed for gilthead sea bream reduced feed price and diet costs by 5.7% per kg and feeding cost per day by approximately 9% compared to the control diet, and this reduction was mainly attributed to the improved feed efficiency (Diógenes et al, 2018).…”
Section: Economic Contribution Of Ddgs On Feedsmentioning
confidence: 86%
“…Several studies have shown that DDGS partially or fully replace with fish meal or soybean meal in the fish diet positively impacted the growth and reduced the negative impact aquaculture has on the environment (Oliveira et al, 2020), these being attributed to the residual yeast, present during the fermentation, which may have some effect on the fish development by quickening the maturation of the digestive system, and having prebiotic and probiotic effects, where it is a rich source of nucleic acids, mannan oligosaccharides and β-glucans, and normally protein in DDGS contains around 50% yeast (Goda et al, 2019). Furthermore, fish species, minerals provided by other feed ingredients, and supplementation of deficient nutrients, particularly lysine, all influence the amount of DDGS included in commercial diets (Sándor et al, 2020(Sándor et al, , 2021Révész et al, 2019Révész et al, , 2020Aydın and Gümüş, 2020). One of the most important features of DDGS is the decreased anti-nutritional factors compared to the other plant protein, which is useful for fish growth, and might have a role in the improvement in growth (Gümüş et al, 2016).…”
Section: Effects On the Growth Of Fish And Crustaceansmentioning
confidence: 99%
“…Ex Spreng) pulp oil (Porto et al, 2020b). Fish pigmentation is associated with the fish species, the ability of the dye to pigment, and the dye concentration in the diet (Yi et al, 2015;Aydın et al 2017;Li et al, 2017), particularly the form of inclusion (Dethlefsen et al, 2016). We must be aware that the search for dyes capable of conferring an increase in blue color is still incipient.…”
Section: /7mentioning
confidence: 99%